CONCEPTUAL MODEL OF INTERCEPTION TO ANTICIPATE RUNOFF - Rina Maharany; J. Bambang Rahadi W; A. Tanggul Sutan Haji (Bernas : Jurnal Penelitian Pertanian, 2016)
Research relating to interception still less, causing need to be done research of interception at some crop types, so that in the end will be gotten interception value magnitude which more specific. Crop applied in this research that is crop Kopi and Pinus. Interception analysis happened at crop will be modeled at equipment of test rainfall simulator. This research is expansion of conceptual model from method SCS ( The Soil Conservation Service) applied for calculation interception based on at various form of crop canopies. The purpose of thisobservation is : 1) Develops interception model as characteristic function of rain and farm closing characteristic, 2) Makes interception program to utilize Visual Basic 60, 3) co-signature big interception for crop Kopi and Pinus. Result of research it is known that interception at crop Kopi bigger than interception of crop Pinus with maximum storage potency value ( Sv) for crop Kopi 2,66 cm and Pinus 1,24 cm, and value Canopy Coefficient ( CC) for crop Kopi is 7,89 andPinus 8,89. Result of verification of modelling as according to example of calculation using method SCS ( The Soil Conservation Service) and Microsoft Excel. Keywords: Rainfall Simulator, Interception, metode SCS and canopy coefficient